Do surgical margins matter after mastectomy? A systematic review. Issue 12 (December 2020) - Bundred, James; Michael, Sarah; Bowers, Sarah; Barnes, Nicola; Jauhari, Yasmin; Plant, Dafydd; Maishman, Thomas; Cutress, Ramsey; Holleczek, Bernd; Dodwell, David; Bundred, Nigel
Abstract: Background: No consensus exists regarding adequacy of margins after mastectomy. To determine if pathological margin proximity is associated with local (LR) or distant recurrence after mastectomy for early invasive breast cancer or ductal carcinoma in situ. Methods: A systematic review of literature published from 1980 to 2019 and meta-analysis was conducted. Unpublished data were sought from authors (PROSPERO (CRD42019127541)). Thirty-four studies comprising 34, 833 breast cancer patients were included in the quantitative synthesis. Eligible studies reported on patients undergoing curative mastectomy for cancer allowing estimation of outcomes in relation to margin status/width. The association between pathological margin status and local (LR) and distant recurrence was considered using random effects modelling. PRISMA guidelines were followed. Results: Positive margins were associated with increased LR on multivariable analyses (HR, 2·64, (95%CI 2·01–3·46)) and LR was higher regardless of the distance of tumour from the margin defined as positive. After skin-sparing mastectomy, positive margins were associated with increased LR (HR 3·40, (95%CI 1·9–6·2)). In the 4 studies reporting distant recurrence, patients with involved margins had a higher risk (HR 1·53, (95%CI 1·03–2·25)). Conclusions: Failure to achieve clear margins after mastectomy may increase the risks of local and distant recurrence. Adequate margin clearance should be recommended to minimize recurrence after mastectomy in National and International Guidelines.